PowToon pedagogy: Embracing laboratory practices to a virtual environment - Joseph, Jacqueline; Jabi, Mohd Azizul Adzman; William Uyo, Alciey; Alfred, Noel Isaiah; Michelle Jubrin, Elverienna (2022)
PowToon undeniably has an enticing prospect in pedagogical methods. Nonetheless, its persuasiveness in online laboratory teaching and learning delivery is yet to be explored thoroughly by educators. This paper explores the application of PowToon on providing online instructional laboratory practices and assessments on students' return assignments in the form of digital laboratory reports. An animated whiteboard video feature in PowToon is applied to perform the digital content for the instructional laboratory safety guidelines and a step-by-step process of a laboratory experiment. A qualitative descriptive method was used in this study, in which four students were chosen purposively as the study sample. The data were collected using a simple set of questionnaires using the Google Form platform. The majority of the respondents favoured PowToon to be used in an online laboratory and preferred a digital laboratory report as a return assignment. It is highly envisaging that the critical contribution of this study is the solution it provides to address the use of PowToon in the transition of conducting practical works in the traditional laboratory work setting to a technology-enhanced creativity online platform.